The Influence of Location and Price on Shopping Decisions at Practical Gelael Makassar - Andi Irfan; Andi Nuryadin; Pahmi; Andi Alim (Jurnal Economic Resource, 2023)
The important factors considered in choosing the location of each supermarket are different. For a supermarket or mini market, the most important factor is being close to consumers. To achieve the goals of a good marketing company, it is necessary to have the right marketing strategy, including pricing by paying attention to changes in consumer behaviour. This study aims to determine the effect of location and price on shopping decisions at Gelael Practical Makassar. This study uses quantitative analytical research methods. The results of this study found that location and price had a significant effect on shopping decisions; Price has a significant effect partially on shopping decisions. Price is the main variable that influences consumer evaluation of the product to be purchased; Meanwhile, the results of multiple linear regression analysis show that consumer decisions are more influenced by price than location, in shopping decisions at Gelael Practical Makassar. It is recommended that the company can pay attention to other factors that exist to further improve the shopping decision.